Performance of Gallium-Erbium Fiber Amplifier in a Double-Pass Configuration - Ibrahim, Siti Azlida; Samsudin, Syafiq Irfan; Mansoor, Amilia; Musa, Siti Musliha Aishah; D. Dambul, Katrina; Md. Yusoff, Nelidya; Abdul Rashid, Hairul Azhar (International Journal of Integrated Engineering, 2024)
In a previous amplifier setup, a Gallium co-doped Erbium fiber (Ga-EDF) with a length of 2 m has been used as a gain medium. The amplifier which was designed as a single-pass configuration, achieving a highest gain of 22.45 dB. In this paper, the Ga-EDF amplifier is designed as a double-pass setup. The gain and noise figure at the input signal’s wavelength of 1520 nm - 1580 nm is investigated at various input powers, which are from -30 dBm to 0 dBm. This study compares the performance of the amplifiers as it is pumped by a laser signal at the wavelength of 980 nm and 1480 nm, with a power of 140 mW. The amplifier obtained the highest gain of 36.62 dB and 35.77 dB for the pump wavelength of 980 nm and 1480 nm, respectively. The corresponding noise figures are 3.48 dB and 5.01 dB, which occurs at the input signal’s wavelength of 1555 nm. The results indicate that the double-pass Ga-EDF amplifier pumped at 1480 nm outperforms the single pass Ga-EDF amplifier by 15.08 dB, with a comparable noise figure. The results also show that the double-pass Ga-EDF’s performance are comparable at both pump wavelengths.